EVALUATION AND STUDIES ON THE STRUCTURAL IMPACT OF SUBSTITUTED 4, 5-DIHYDROISOXAZOLES ON THEIR BIOLOGICAL ACTIVITIES (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
In present study, a series of isoxazole derivatives synthesized were evaluated for antimicrobial activities by disc diffusion method. Some compounds of the series exhibited promising antibacterial and antifungal activity compared to standard drugs. The minimum inhibitory concentration (MIC’s) was determined against each organism. The compounds were tested for their in-vitro antioxidant activity and reducing power ability. Free radicals play an important role in various pathological and xenotoxic effects so antioxidant may have protective role in these pathological conditions. Based on the results of an antimicrobial, anti-oxidant study, the effect of substitution on the activity and possible structure activity relationship of the compounds for their antioxidant activity is presented.